PENGARUH LAMA PENGGUNAAN KONTRASEPSI DMPA (DEPOMEDROXI PROGESTERON ASETAT) TERHADAP PENURUNAN LIBIDO PADA WANITA USIA SUBUR DI BPM LUKLUATUN MUBRIKOH S.ST - Siti Rochimatul Lailiyah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Decrease in libido is often found in injection KB users. Seen from the preliminary study, there were 6 people (60%) who experienced a decrease in libido. Purpose of the study Analyze the effect of long-term DMPA contraception use on decreasing libido in women of childbearing age. The design of this study used analytical survey with a cross sectional approach. The independent variable is the duration of use of DMPA contraseption. The dependent variable is libido, the population used by all women of childbearing age acceptors who use DMPA contraception from the beginning until now, with a sample of 50 respondents. The technique used is Probability Sampling using simple random sampling, the tool used for data collection is a questionnaire then analyzed using the Spearman Rank test proceed with the Z score. The results of statistical tests with Spearman rank based on Rank Spearmen statistical test obtained the value of P-Value (0.016) <α (0.05) followed by Z score (0.112) which means that there is an effect DMPA contraseption usage time on decreased libido in women of childbearing age . It should be noted that the use of hormonal contraseption especially for DMPA so as not to disturb the body system. At least if you have taken 2 years, you are advised to use non-hormonal contraception.